Synergistic toughening of welds through adding SiC nanoparticles and modulating oscillating laser - Mingjun Zhang; Rui Wang; Xiaobing Pang; Jian Zhang; Cong Mao; Bo Cheng; Longzhou Dai; Heqing Li; Jing Guo; Zhuming Bi (Journal of Materials Research and Technology)
To enhance the strengths of welds on AZ31B Mg alloy, silicon carbide (SiC) nanoparticles can be added in welds to improve mechanical properties of welds. However, SiC nanoparticles have high-level of surface energy, the physical properties of SiC nanoparticles are significantly different from Mg alloy, and these tend to cause the instability of a molten pool and a keyhole in laser-welding. This study proposed to modulate the power of an oscillating laser and control the temporal and spatial distribution of laser energy to strengthen welds when SiC nanoparticles are applied to join AZ31B Mg alloy. The effects of power modulation on macroscopic morphology, microstructure, and mechanical properties of welds were investigated systematically. The experiments showed that an oscillating laser with the modulated power has not only reduced various defects including spatters, weld beads, and humping significantly; but also decreased gas porosities in welds and eliminated an agglomeration of nanoparticles. At a modulation frequency of 150 Hz, the average size of grains was refined from 24.30 to 5.87 μm, and the maximum intensity at the 0001 direction of texture had a reduction over 86%. By comparing with the mechanical properties of base materials, the ultimate tensile strength was increased to 239 MPa (96.3%) and the elongation at the fracture point reaches 12.75% (53.5%). By comparing the welds by the laser welding without (i) adding nanoparticles and (ii) power modulation, the proposed method has increased the tensile strength by 12.7% and 10.1% and the elongation by 45.9% and 20.9%, respectively.